Ocular Phenotype of a Family with FAM161A-associated Retinal Degeneration. (2nd January 2016) - Duncan, Jacque L.; Biswas, Pooja; Kozak, Igor; Navani, Mili; Syed, Reema; Soudry, Shiri; Menghini, Moreno; Caruso, Rafael C.; Jeffrey, Brett G.; Heckenlively, John R.; Reddy, G. Bhanuprakash; Lee, Pauline; et al.
Abstract: Background : Characterization of retinal degeneration (RD) using high-resolution retinal imaging and exome sequencing may identify phenotypic features that correspond with specific genetic defects. Materials and Methods : Six members from a non-consanguineous Indian family (three affected siblings, their asymptomatic parents and an asymptomatic child) were characterized clinically, using visual acuity, perimetry, full-field electroretinography (ERG), optical coherence tomography and cone structure as outcome measures. Cone photoreceptors were imaged in the proband using adaptive optics scanning laser ophthalmoscopy. The exome was captured using Nimblegen SeqCap EZ V3.0 probes and sequenced using lllumina HiSeq. Reads were mapped to reference hg19. Confirmation of variants and segregation analysis was performed using dideoxy sequencing. Results : Analysis of exome variants using exomeSuite identified five homozygous variants in four genes known to be associated with RD. Further analysis revealed a homozygous nonsense mutation, c.1105 C > T, p.Arg335Ter, in the FAM161A gene segregating with RD. Three additional variants were found to occur at high frequency. Affected members showed a range of disease severity beginning at different ages, but all developed severe visual field and outer retinal loss. Conclusions : Exome analysis revealed a nonsense homozygous mutation in FAM161A segregating with RD with severe vision loss and a range of disease onset and progression. Loss of outer retinal structures demonstrated with high-resolution retinal imaging suggests FAM161A is important for normal photoreceptor structure and survival. Exome sequencing may identify causative genetic variants in autosomal recessive RD families when other genetic test strategies fail to identify a mutation.